2012
DOI: 10.1021/jp307725z
|View full text |Cite
|
Sign up to set email alerts
|

Photochemistry of UV-Excited Trifluoroacetylacetone and Hexafluoroacetylacetone I: Infrared Spectra of Fluorinated Methylfuranones Formed by HF Photoelimination

Abstract: The photochemistry of gas-phase 1,1,1-trifluoroacetylacetone (TFAA) excited with ultraviolet (UV) light involves a significant photoelimination channel that produces hydrogen fluoride and a fluorinated methylfuranone, 2,2-difluoro-5-methyl-3(2H)-furanone (2FMF). This pathway is remarkable because it is a gas-phase unimolecular reaction that forms a five-membered ring product. This report is the first of such a TFAA photoelimination channel, which is similar to one observed with 1,1,1,5,5,5-hexafluoroacetylacet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…We thus expect the reaction path to be similar to that of HFAAc, i.e., rotation to a hydrogen bonded intermediate promoting HF loss and the formation of [M À HF] À in the furanone form. In fact this reaction was also observed for neutral TFAAc in a recent photolysis study by Muyskens et al 37 From TFAAc, we also observe [M À 2HF] À (Fig. 7b) and HF 2 À (Fig.…”
Section: Triuoroacetylacetonesupporting
confidence: 88%
See 1 more Smart Citation
“…We thus expect the reaction path to be similar to that of HFAAc, i.e., rotation to a hydrogen bonded intermediate promoting HF loss and the formation of [M À HF] À in the furanone form. In fact this reaction was also observed for neutral TFAAc in a recent photolysis study by Muyskens et al 37 From TFAAc, we also observe [M À 2HF] À (Fig. 7b) and HF 2 À (Fig.…”
Section: Triuoroacetylacetonesupporting
confidence: 88%
“…This argument was later supported by a tandem-chemical laser spectroscopy study by Pimentel et al 36 who detected the neutral HF formed in the reaction. Recently, Muyskens et al 37 showed that this reaction is also observed in photolysis of triuoroacetylacetone (TFAAc), but the corresponding reaction leading to the formation of H 2 from AAc was not observed. In a sense, electron excitation from a bonding to an antibonding orbital is comparable to electron capture to the same antibonding orbital in DEA.…”
Section: Multiple Bond Ruptures and Rearrangement Reactionsmentioning
confidence: 99%
“…We also note that the TCC rotamer has been suggested as a precursor to the transition state for the proposed photodissociation pathway to form HF + pentafluoromethyl-3-furanone. 17 Despite this, the possible pentafluoromethyl-3-furanone (PF3F) product, is not observed in the experimental spectrum. The PF3F molecule in the S 0 ground state is predicted by ROKS to have a C K-edge spectrum very similar to HfAcAc ground state (as shown in Figure S6).…”
Section: ■ Methodsmentioning
confidence: 81%
“…Although the presence of trifluoromethyl groups on the chelated ring weakens the HB, the enol form remains dominant in the gas phase. Recently Muyskens et al [8] showed that both TFAA and HFAA undergo gas-phase HF elimination upon UV excitation, whereas the analogous H 2 elimination pathway in AA is not evident. Further understanding of the role that fluorine atoms play in the HB strength and the HF elimination pathway leads to our interest in 1-fluoro-pentane-2,4-dione (monofluoroacetylacetone, MFAA), which is the focus of this paper.…”
Section: Introductionmentioning
confidence: 99%
“…The questions then are which isomer with an asymmetric fluorine distribution will be favored, and is the strength of the HB simply related to the number of fluorine atoms? Scheme 2 shows the proposed mechanism for the gas phase photoelimination reaction of TFAA and HFAA reported by Muyskens et al [8] adapted for MFAA. In this scheme, the orientation of the IHB is such that proton transfer is not required before C2-C3 rotation brings the fluorine atom into proximity of the proton leading to elimination.…”
Section: Introductionmentioning
confidence: 99%